Riding the Real Estate Wave Along Maine's Coast - Swanson, Ryan (Maine Policy Review, 2023)
A review of Maine's coastal real estate market that explores the reason why the area is so appealing, to whom, and what that means.
Keywords: coastal real estate; housing market